Do patients with cervical dystonia present a greater risk and more fear of falling? - Takeda, Sibele Yoko Mattozo; Souza, Ana Félix de; Penteado, Iara Ferreira; Veronez, Djanira Aparecida da Luz; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2025)
Background Cervical dystonia (CD) is a movement disorder characterized by involuntary contractions that affect the muscles of the cervical region, causing movements in a twisting pattern. Its chronic-progressive nature can lead to pain, impaired mobility, and greater propensity to falls.Objective To verify gait and balance characteristics and their correlation with the risk and fear of falling in 46 CD patients.Methods The present was a descriptive and cross-sectional study. For the assessments, we sued the Berg Balance Scale (BBE), the Tinetti Scale (also known as the Performance-Oriented Mobility Assessment, POMA), the Dynamic Gait Index (DGI), the Fall Efficacy Scale-International (FES-I), and the Functional Reach Test (FRT). The patients were recruited during their routine consultations, before the administration of botulinum toxin. For data analysis, we used the BioEstat 5.0 software (free) to verify the distribution of samples (Shapiro-Wilk test) and the correlations among variables (Spearman test) considering p ≤ 0.05%.Results The results showed that the patients presented gait changes related to static and dynamic components of balance. Therefore, we observed a greater propensity to falls, with a correlation involving lack of balance, a greater risk of falling and, consequently, more fear of falling.Conclusion We verified that changes in the balance of CD patients have a negative impact on gait, increase the risk and the fear of falling, and can lead the individual to restrict their activity levels.
Keywords: Dystonia; Postural Balance; Gait; Rehabilitation